Studi Pertumbuhan Miselia Jamur Merang (Volvariella volvaceae) G2 Isolat FP005 Faperta UNSIKA Pada Beberapa Bahan Alternatif Media In Vitro - Aisyah Nur Rustaman; Bastaman Syah; Nurcahyo Widyodaru; Ani Lestari (UNIVERSITAS LABUHANBATU, 2023)
Straw mushroom is one of the horticultural commodities that is in great demand by the community. The successful cultivation of straw mushrooms is determined by the quality of the seeds of the molten mushroom. Tissue culture is one of the efforts to get quality seeds. Quality seedlings are seen from the brood of the merang fungus and the quality of pure culture. Making pure culture is still constrained in making in vitro media, especially alternative media materials. This study aims to obtain the best results from the growth of G2 FP005 mycelia on alternative media materials in vitro. This research was conducted at the Biotechnology and Plant Breeding Laboratory, Faculty of Agriculture, Singaperbangsa University, Karawang from April to May 2023. The research method used was a single factor Complete Randomized Design (CRD) with 7 treatments and 5 replications: A (100% PDA); B (100% Charcoal Husk Solution); C (100% Husk Solution); D (80% PDA + 20% Husk Charcoal Solution), E (75% PDA + 25% Husk Solution), F (50% Husk Charcoal Solution + 50% Husk Solution); G (50% PDA + 25% Husk Charcoal Solution + 25% Husk Solution). The effect of the treatment was analyzed using variance and if the F test was significant at 1% level, then to find out which treatment was the best it was continued with the DMRT (Duncan Multiple Range Test) advanced test at the 1% level of significance. The results achieved from this study were that there was a significant effect of using alternative media materials on the growth of the straw mushroom mycelia. Alternative media 80% PDA + 20% rice husk charcoal gave the highest mycelia colony diameter of 7.88 cm and the highest mycelial colony growth rate of 2,878 cm/day. Keywords: Unsika Faperta Isolate, Straw Mushroom, Tissue Culture.